2017
DOI: 10.1111/1756-185x.13071
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and long‐term outcomes of 105 granulomatosis with polyangiitis patients: A single center experience from north India

Abstract: Aim: To describe the clinical features, treatment and long-term outcomes in north Indian patients with granulomatosis with polyangiitis (GPA).Methods: Clinical details, Birmingham Vasculitis Activity Score (BVAS-v3), laboratory data, histopathology findings, treatment details and outcomes of all consecutive patients diagnosed as having GPA between April 2005 and April 2016 were retrieved. European Vasculitis Study Group definitions were used to classify patients into localized, early systemic, generalized, sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 10 publications
2
28
0
1
Order By: Relevance
“…The conventional understanding of granulomatosis with polyangiitis (GPA) in Asia was influenced by studies from Japan, which suggested MPO‐positive GPA as a dominant phenotype in Asia. This understanding was recently expanded by reports of PR3‐positive GPA from India . Our group also showed that renal involvement is milder and does not portend a poor prognosis .…”
supporting
confidence: 59%
“…The conventional understanding of granulomatosis with polyangiitis (GPA) in Asia was influenced by studies from Japan, which suggested MPO‐positive GPA as a dominant phenotype in Asia. This understanding was recently expanded by reports of PR3‐positive GPA from India . Our group also showed that renal involvement is milder and does not portend a poor prognosis .…”
supporting
confidence: 59%
“…A comparison of 657 AAV patients included in clinical trials vs 437 followed up in observational cohorts worldwide revealed that those included in clinical trials were older and had more severe disease at baseline; the clinical trial subjects with GPA but not MPA had greater mortality and relapses in comparison to the real‐world patients . It had been commonly believed that Asian patients (mostly from Japanese cohorts) with GPA have greater MPO‐ANCA positivity than Caucasian patients; however, a recent large cohort of GPA from North India challenged this conventional thinking, with a greater proportion of PR3‐ANCA than MPO‐ANCA positive patients in this cohort …”
Section: Anca Vasculitismentioning
confidence: 99%
“…The prevalence among Iranian children younger than 15 years was estimated to be 0.6/million . Even though various case series on GPA have been described from India, Korea and other Asian countries, none of them has estimated the prevalence or incidence of GPA …”
Section: Epidemiologymentioning
confidence: 99%